THE COVERAGE OF PROBLEMS IN FAMILY LIFE CAUSED BY THE BIRTH OF A MENTALLY ILL CHILD IN THE SCIENTIFIC LITERATURE - Nurmukhammedova, L.Sh. (International Journal of Psychosocial Rehabilitation, 2020)
Problems of maintenance of disabled children social and household education are revealed in the article. The independence goals at present require innovation of the special training and education system contents. Introductions of scientifically and theoretically based researches, researches and findings of the new methods and ways of household and social successive relationship are prior and actual for special pedagogy.